Racial/ethnic disparities in the enrollment of Medication Therapy Management programs among Medicare beneficiaries with Alzheimer's disease and related dementias. (3rd October 2022) - Browning, Jamie A.; Tsang, Chi Chun Steve; Zeng, Rose; Dong, Xiaobei; Garuccio, Joseph; Wan, Jim Y.; Chisholm-Burns, Marie A.; Finch, Christopher K.; Tsao, Jack W.; Wang, Junling
Abstract: Objective: Previous analysis of policy scenarios reported potential disparities in eligibility in the Medicare Medication Therapy Management (MTM) program. With recently released MTM data, this study aimed to determine if racial/ethnic disparities exist in MTM enrollment among Medicare beneficiaries with Alzheimer's disease and related dementias (ADRD). Methods: Medicare claims/records (from 2013–2014 and 2016–2017) linked to the Area Health Resources File were examined. Included individuals were patients with ADRD and diabetes, hypertension or hyperlipidemia. The proportions of MTM enrollment were compared between non-Hispanic White (White) patients and racial/ethnic minority groups in descriptive analysis. Racial/ethnic disparities were then examined using a logistic regression adjusting for patient and community characteristics. Disparities across study periods were compared by estimating a logistic regression model with interaction terms between dummy variables for each racial/ethnic minority group and 2016–2017. Results: In unadjusted analyses, minorities had higher enrollment proportions than Whites. In 2016–2017, for example, enrollment percentages for Whites, Blacks, Hispanics, Asian/Pacific Islanders (Asians) and Others were respectively 14.44%, 16.71%, 19.83%, 16.66%, and 17.78%. In adjusted analyses, Blacks had lower enrollment odds than Whites within all cohorts. In the entire study sample in 2016–2017, for example, Blacks with ADRD had 9% lower odds of MTM enrollment (odds ratio 0.91, 95% confidence interval [CI] = 0.86–0.97) than Whites. These disparities decreased over time among the ADRD sample and all sub-groups. The interaction term between Blacks and 2016–2017, for instance, indicated that disparities were lowered by 11% (odds ratio 1.11, 95% CI = 1.05–1.16) across study periods among those with ADRD. Conclusions: Blacks with ADRD, and diabetes, hypertension or hyperlipidemia have lower likelihood of MTM enrollment than Whites. Racial disparities were reduced over time but not eliminated.